Lifelines: Desistance, Social Relations, and Reciprocity. (January 2015) - Weaver, Beth; McNeill, Fergus
This article draws on the life stories of a friendship group of men in their 40s who offended together in their youth and early adulthood. By exploring these interrelated narratives, we reveal individual, relational, and structural contributions to the desistance process, drawing on Donati's relational sociology. In examining these men's social relations, this article demonstrates the central role of friendship groups, intimate relationships, families of formation, employment, and religious communities in change over the life course. It shows how, for different individuals, these relations triggered reflexive evaluation of their priorities, behaviors, and lifestyles, but with differing results. However, despite these differences, the common theme of these distinct stories is that desistance from crime was a means of realizing and maintaining the men's individual and relational concerns, with which continued offending became (sometimes incrementally) incompatible. In the concluding discussion, we explore some of the ethical implications of these findings, suggesting that work to support desistance should extend far beyond the typically individualized concerns of correctional practice and into a deeper and inescapably moral engagement with the reconnection of the individual to social networks that are restorative and allow people to fulfill the reciprocal obligations on which networks and communities depend.